King & Kayla and the case of the lost tooth - Butler, Dori Hillestad (Butler, Dori Hillestad. King & Kayla., 2018)
Kayla places her tooth in a Tooth Fairy pillow, but it disappears before the Tooth Fairy has a chance to visit--can her dog King help Kayla find the missing tooth?